Peran Fasilitator Pendamping dan Teknologi Keuangan terhadap Pengelolaan Keuangan Ibu Pelaku UMKM di Kecamatan Sakra Timur Kabupaten Lombok Timur - Idayani, Idayani; Sulkiah, Sulkiah (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of facilitator roles and financial technology on the financial management of women micro, small, and medium enterprise (MSME) entrepreneurs in Sakra Timur District, East Lombok Regency. A quantitative method with a survey research design was used in this study. Data were collected through questionnaires distributed to 100 respondents who were women MSME entrepreneurs in the area. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables (facilitator roles and financial technology) and the dependent variable (financial management). The results showed that the role of facilitators had no significant effect on the financial management of women MSME entrepreneurs. These findings indicate that the utilization of financial technology can improve financial management among MSME actors, whereas the facilitator role does not make a significant contribution.